Barriers to the Diagnosis, Care, and Management of Pediatric Patients With Ehlers-Danlos Syndrome in the United States: A Qualitative Analysis - William R. Black PhD; Lora L. Black PhD; Jordan T. Jones DO (Global Pediatric Health, 2023)
Objectives: Ehlers-Danlos Syndromes (EDS) are a family of heritable connective tissue diseases. Primary practitioners are capable of diagnosing and managing EDS; however, few are knowledgeable and comfortable enough to see patients with EDS, resulting in delays in diagnosis and care. This study explores the barriers physicians experience with diagnosing, managing, and caring for patients with EDS, and potential resolutions to those barriers. Methods : As part of a larger online study, providers (n = 107) in the United States were asked to specify “What information would improve (their) comfort” in diagnosing, caring for, and managing EDS via open-ended questions. Results : Providers reported wanting clinical practice guidelines, in formats that were easily accessible and usable, information on their roles in the management of EDS, the best ways to coordinate with specialty care, and available specialty consultation. Conclusions : Providers overall are willing to diagnose and treat EDS; however, additional supports and training are needed.